Mass transfer characteristics according to flow field and gas diffusion layer of a PEMFC metallic bipolar plate for stationary applications. (1st January 2023) - Park, Donghwan; Ham, Seonghyeon; Sohn, Young-Jun; Choi, Yoon-Young; Kim, Minjin
Abstract: Recently, to reduce the unit cost of fuel cells for large-capacity stationary applications, metallic bipolar plates are attracting interests. Due to the different operating conditions such as the current range and water generation of fuel cells for stationary applications, a shape different from that of the previously developed metal bipolar plate for vehicles is required. The smooth supply of reactants and removal of products within the fuel cell is essential to secure high fuel-cell performance. The mass transfer of reactant and product in a fuel cell is performed mainly by the flow field and gas diffusion layer. In this study, fuel-cell mass transfer characteristics according to the geometry of the metallic bipolar plate flow-field and the gas diffusion layer in the fuel-cell operating condition for stationary applications were analyzed based on a computational fluid dynamics model and verified experimentally. The channel-type flow path and some metal foams were used as the flow field and several types of gas diffusion layers with different porosity and permeability were used. The water removal effect increased by 6.55% when the channel was replaced by the metal foam as the flow field. It was also verified that the fuel cell performance improved by 9.33%. In addition, the fuel cell performance increased by 14.67% when a gas diffusion layer with high porosity and permeability was used. Highlights: Performance of the fuel cell with metallic separators is simulated using models. Modeling results are verified by changing the geometry of the flow fields and GDL. Fuel cell performance is improved by 14.67% after optimizing the geometry.